Evaluating Breast Reconstruction Reviews Using A Measurement Tool to Assess Systematic Reviews (AMSTAR). Issue 11 (November 2021) - Yuan, Morgan; Wu, Jeremy; Austin, Ryan E.; Hofer, Stefan O.P.; Lista, Frank; Ahmad, Jamil
Abstract : Background: Breast reconstruction is an important aspect in breast cancer treatment. Methods: A comprehensive search of MEDLINE, Embase, and the Cochrane Library of Systematic Reviews was performed. Systematic reviews and meta-analyses that focused on breast reconstruction and were published between 2000 and 2020 were included. Quality assessment was performed using A Measurement Tool to Assess Systematic Reviews (AMSTAR). Study characteristics were extracted, including journal and impact factor, year of publication, country affiliation, reporting adherence to Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines, number of citations, and number of studies included. Results: The average AMSTAR score was moderate (5.32). There was a significant increase in AMSTAR score ( P < 0.01) and number of studies ( P < 0.01) over time. There were no significant correlations between AMSTAR score and impact factor ( P = 0.038), and AMSTAR score and number of citations ( P = 0.52), but there was a significant association between AMSTAR score and number of studies ( P = 0.013). Studies that adhered to the PRISMA statement had a higher AMSTAR score on average ( P < 0.01). Conclusions: Systematic reviews and meta-analyses about breast reconstruction had, on average, a moderate AMSTAR score. The number of studies and methodological quality have increased over time. Study characteristics including adherence to PRISMA guidelines are associated with improved methodological quality. Further improvements in specific AMSTAR domains would improve the overall methodological quality.